The Phenomenon of Internet Addiction Disorder Online Gambling In Probolinggo - Nining Winarsih; Sofia Salsabila (IAIN Madura, 2022)
Information and communication technology in the 5.0 era is massive and make changes to people's lives. There are many positive impacts from the internet, but there are also negative impacts causing problematic behavior in society such as online gambling. This study uses a phenomenological type of qualitative approach. The sample used in this purposive sampling study was the active students of Probolinggo Regency. Data collection techniques used by researchers in this study were observation, in-depth interviews, and documentation. Testing the validity of the data in this study using source triangulation techniques. Analyzing the data obtained carried out several stages, namely data collection, data reduction, data presentation, and verification/drawing conclusions. The results of the study show that online gambling has a negative and positive impact on the lives of Probolinggo students who are already familiar with online gambling. The negative impacts felt by Probolinggo students in their lives such as decreased learning achievement, resulting in addiction, and lack of socializing with family. not only has a negative impact, but also has a positive impact on the lives of its users (students) such as getting big profits. This research is recommended to the public, especially educators and students, to be more aware of the phenomenon of addiction disorder which is quite worrying. Keywords: online gambling, student, internet